The impacts of adult HIV/AIDS mortality on elderly women and their households in rural South Africa - Ogunmefun, Catherine Ajibola (My University, 2009)
This thesis examines the impacts of adult HIV/AIDS related mortality on elderly women and their households in Agincourt, a rural area in the north-eastern part of South Africa. It focuses specifically on demographic, socio-economic and socio-cultural impacts of adult AIDS and non-AIDS illness/death on near-old women aged 50-59 and older women aged 60 and above. The study uses the Agincourt Health and Demographic Surveillance System (AHDSS) 2004 census data which contains some history about individuals and their households (e.g. household mortality experience between 1992 and 2004). The AHDSS dataset is used to examine elderly female household headship and its relationship with, firstly, pension status and secondly, adult AIDS/non-AIDS mortality, through statistical analyses. Also, the AHDSS census data is utilised as a sampling frame to select a random sample of 60 households in which 30 women aged 50-59 and 30 women aged 60-75 lived, for the qualitative part of this study. The sample was made up of 20 women who lived in households that had experienced an HIV/AIDS death between 2001 and 2003, 20 women that lived in households where another type of adult death had occurred, and 30 women in households with no adult death during the period. The findings from the quantitative analyses of the AHDSS dataset reveal that there is no significant relationship between adult AIDS/non-AIDS death and elderly female household headship. Further findings, however, show that elderly female household headship is strongly associated with pension status, thereby suggesting that pension grant is a determining factor in the household headship status of elderly women. One implication of this is that elderly female household heads who are pensioners may be able to cope better with HIV/AIDS impacts as findings from the qualitative data demonstrate that pensioners (older women) are more likely, than non-pensioners (near-old women), to have access to coping strategies, which enable them to deal with the financial crises of adult illness/death in their households. There is, therefore, the need for programmes to target near-old women, who experience the financial impact of adult morbidity/mortality like their older peers. iii Further findings from the qualitative data explicate secondary stigma as a socio-cultural impact of adult HIV/AIDS on elderly women who are caregivers to infected children. Findings also highlight different types of secondary stigma such as physical stigma in the form of separation from family members and social stigma in the form of social isolation. The study suggests that there is need for intervention programmes that address the issue of secondary stigma as it makes caregiving responsibilities more burdensome for elderly women.
Keywords: adult HIV/AIDS mortality; HIV impact; verbal autopsy data; socio-economic impact; elderly women